Nanoporous Metal Phosphonate Hybrid Materials as a Novel Platform for Emerging Applications: A Critical Review. Issue 22 (19th February 2021) - Lv, Xian‐Wei; Weng, Chen‐Chen; Zhu, Yun‐Pei; Yuan, Zhong‐Yong
Abstract: Nanoporous metal phosphonates are propelling the rapid development of emerging energy storage, catalysis, environmental intervention, and biology, the performances of which touch many fundamental aspects of portable electronics, convenient transportation, and sustainable energy conversion systems. Recent years have witnessed tremendous research breakthroughs in these fields in terms of the fascinating pore properties, the structural periodicity, and versatile skeletons of porous metal phosphonates. This review presents recent milestones of porous metal phosphonate research, from the diversified synthesis strategies for controllable pore structures, to several important applications including adsorption and separation, energy conversion and storage, heterogeneous catalysis, membrane engineering, and biomaterials. Highlights of porous structure design for metal phosphonates are described throughout the review and the current challenges and perspectives for future research in this field are discussed at the end. The aim is to provide some guidance for the rational preparation of porous metal phosphonate materials and promote further applications to meet the urgent demands in emerging applications. Abstract : Nanoporous metal phosphonates have shown great potential in facilitating functionality, shapeability, combination, and miniaturization, which offer a multifunctional platform to make breakthroughs in many promising application fields, such as optics, electronics, ionics, membranes, and catalysis. All the recent developments in designing these porous metal phosphonates are summarized here with a special emphasis on the porosity‐property‐functionality relationships.